2016
DOI: 10.1089/lap.2016.0308
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Common Bile Duct Exploration Versus Open Approach in Cirrhotic Patients with Choledocholithiasis: A Retrospective Study

Abstract: LCBDE can be safely performed in patients with Child-Pugh A or B cirrhosis and choledocholithiasis, with considerable efficiency, minimal short-term complications, and acceptable long-term outcomes. LCBDE has the advantages over open CBD exploration of less bleeding and reduced length of hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Studies that compared the operative time between LCBDE and OCBDE showed mixed results that mostly were statistically insignificant. 22,25,32,33,53 On the other hand, laparoscopic transcystic approach has been reported to have shorter mean operative time than the laparoscopic transductal approach as we have discussed earlier in the text.…”
Section: Transcysticmentioning
confidence: 86%
See 3 more Smart Citations
“…Studies that compared the operative time between LCBDE and OCBDE showed mixed results that mostly were statistically insignificant. 22,25,32,33,53 On the other hand, laparoscopic transcystic approach has been reported to have shorter mean operative time than the laparoscopic transductal approach as we have discussed earlier in the text.…”
Section: Transcysticmentioning
confidence: 86%
“…The referencing order of the studies included in Table 2 starts from the most recently published papers. 19-54 Grading of the reviewed evidence was based on the content of Table 3. Statistical difference significance was considered to be P ≤ .05.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[5] However, some recent studies proved laparoscopic CBD exploration to be successful in older and cirrhotic patients. [22][23][24] Among our patients, serious secondary conditions were observed in 28.3% cases, including pregnancy in four patients, cirrhosis in four patients and older age in seven patients, and no complication was identified regarding such conditions. Impacted stones comprise the main reasons of failures both in laparoscopic and endoscopic managements.…”
Section: Discussionmentioning
confidence: 70%